"The Mother of Reason and Revelation": Benjamin on the Metaphysics of Language. Issue 2 (3rd April 2018) - Stern, Alexander
ABSTRACT: This paper is a reconstruction of Walter Benjamin's philosophy of language, especially as it expressed in 1916's "On Language as Such and the Language of Man". I read Benjamin's theory as a contribution to what Charles Taylor has called the "expressivist" tradition that includes eighteenth century thinkers like J.G. Herder and J.G. Hamann. Hamann's work and his interpretation of the theological concept of condescension are of particular importance. Although Benjamin's views are often regarded as impenetrable or mystical, they are relevant to and, in part, motivated by concerns of more mainstream twentieth century philosophy of language, in particular Russell's paradox. His "metaphysics of language" understands reference or designation, central to analytic theories of meaning, as derived from a more fundamental, aesthetic meaning.